Unusual Bilateral Rim Fracture in Femoroacetabular Impingement - Claudio Rafols; Juan Edo Monckeberg; Jorge Numair (Case Reports in Orthopedics)
This is a report of one case of bilateral acetabular rim fracture in association with femoroacetabular impingement (FAI), which was treated with a hip arthroscopic procedure, performing a partial resection, a labral reinsertion, and a subsequential internal fixation with cannulated screws. Up to date, there are in the literature only two reports of rim fracture and “os acetabuli” in association with FAI. In the case we present, the pincer and cam resection were performed without complications; the technique used was published previously. With this technique the head of the screw lays hidden by the reattached labrum. We removed partially the fractured rim fragment and the internal fixation of the remaining portion was achieved with a screw. In the event of a complete resection of the fragment, it would have ended with a LCE angle of 18° and a high probability of hip instability. We believe that this bilateral case helps establish the efficacy and reproducibility of the technique described by Larson.